Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1007/s00425-004-1313-7
|View full text |Cite
|
Sign up to set email alerts
|

C-Terminal 23�kDa polypeptide of soybean Gly�m�Bd 28�K is a potential allergen

Abstract: Gly m Bd 28 K is a major soybean (Glycine max Merr.) glycoprotein allergen. It was originally identified as a 28 kDa polypeptide in soybean seed flour. However, the full-length protein is encoded by an open reading frame (ORF) of 473 amino acids, and contains a 23 kDa C-terminal polypeptide of as yet unknown allergenic and structural characteristics. IgE-binding (allergenic potential) of the Gly m Bd 28 K protein including the 23 kDa C-terminal portion as well as shorter fragments derived from the full-length … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 31 publications
2
44
0
4
Order By: Relevance
“…There is very little additional information about variation in this allergen among different soybean genotypes. A mutant line of soybean G. max, cv Tohoku 124, with the absence of β-conglycinin also lacks Gly m Bd 28 K. 30 Xiang et al 39 demonstrated that both the Nand C-terminal fragments of Gly m Bd 28 K can bind IgE, and have characterized a novel dominant sequential epitope on the C-terminal fragment of the protein. Tsuji et al 40 reported that Gly m Bd 28 K was about twice as large as anticipated from its initial discovery as a 28 kDa polypeptide by onedimensional SDS-PAGE.…”
Section: Analysis Of Gly M Bd 28 K Proteinmentioning
confidence: 98%
“…There is very little additional information about variation in this allergen among different soybean genotypes. A mutant line of soybean G. max, cv Tohoku 124, with the absence of β-conglycinin also lacks Gly m Bd 28 K. 30 Xiang et al 39 demonstrated that both the Nand C-terminal fragments of Gly m Bd 28 K can bind IgE, and have characterized a novel dominant sequential epitope on the C-terminal fragment of the protein. Tsuji et al 40 reported that Gly m Bd 28 K was about twice as large as anticipated from its initial discovery as a 28 kDa polypeptide by onedimensional SDS-PAGE.…”
Section: Analysis Of Gly M Bd 28 K Proteinmentioning
confidence: 98%
“…Approximately 30 g of total protein were loaded from each sample and separated on 12% acrylamide gels in the presence of SDS (Laemmli 1970). Separated proteins were electroblotted to nitrocellulose membranes and probed with antibodies (Xiang et al 2004). Antibodies were generated to soybean root nodule ascorbate peroxidase (Dalton et al 1993) and to recombinant proteins produced in E. coli to the following ESTs: DN143131 = switchgrass CAD; DN143927 = switchgrass CCOMT; CX607415 = sorghum COMT.…”
Section: Immunoblottingmentioning
confidence: 99%
“…Moreover, Gly m Bd 28 K protein shares sequence homology with proteins in pumpkins and carrots (Rihs et al, 1999). Studies revealed a slightly stronger IgE-binding region present in the C-terminal domain of Bd 28K (Xiang et al, 2004) than the N-terminal half of this protein . An important IgE binding region was found in the C-terminal 23 kDa polypeptide, which contains an Asn-N linked moiety with the same sugar composition as that of P34 (Hiemori et al, 2000).…”
Section: Soy Allergensmentioning
confidence: 96%
“…Gly m. Bd 28K is a vicillin-like glycoprotein of 473 amino acids (Xiang et al, 2004), initially isolated from soybean meal as a 28 kDa glycosylated protein. Gly m Bd 28K (Hiemori et al, 2000) constitutes a minor component fractionated into 11S glycinin globulin fraction in soybean seed flour that has been recognized by soybean sensitive patients with about 25% of incidence .…”
Section: Soy Allergensmentioning
confidence: 99%